Effect of carbon nanotube (CNT) additions in Cr3C2-25%NiCr coatings on microstructural and mechanical properties. (2021) - Manjunatha, K.; Giridhara, G.; Jegadeeswaran, N.
Highlights: The experimental investigation carried out on coated samples deposited by the HVOF thermal spray process on the boiler tube substrate. The dense, uniform surface structure is developed, and the presence of elements in the coated samples is confirmed by SEM/EDS, and XRD techniques. The coating with 7% of CNTs content in coating powder exhibited the highest microhardness and low porosity due to carbon nanoparticles fill the porous gap, to improve better functional strength in the coatings. The outcome of the research recommends that by the HVOF process, the addition of CNTs in coatings leads to a strong metallurgical bond strength in the coatings/substrate interface and higher abrasion resistance. Abstract: This research work focuses on Carbon Nanotubes (CNTs) reinforced Cr3 C2 -25%NiCr coating powders, deposited by the HVOF method on ASTM-SA213 T12 thermal power plant boiler tube alloy steel as substrate. The CNTs mixed with coating powder influence on the microstructure, and mechanical properties. The coating powder Cr3 C2 -25%NiCr mixed with CNTs of 3, 5 and, 7% by weight are prepared and deposited on the substrate using the HVOF thermal spray process. In this method the product of burnt fuels expands through the nozzle the gas velocities may be supersonic, the composite coating powder fed axially through the nozzle, their particles heated and accelerated powder particles in a molten or semi-molten state to achieve dense, and adhered coatings impinge on the substrate. The deposited coatings achieve dense, uniform microstructure characterized for surface morphology, and the compositions analyzed by Scanning Electron Microscope (SEM) / Energy Dispersive x-ray Spectroscopy (EDS) analysis. The phase identification of a crystalline material was done using X-Ray Diffraction (XRD) techniques. The coatings reinforced with 7% wt. of CNTs in coated samples exhibit low porosity, highest micro-hardness to maintain high-performance surface properties leading to better mechanical strength in the coatings. In HVOF deposition techniques additions of CNTs in the coatings leads to less porous, carbon nanoparticle fills the pores gap between the coatings, and improve the layer of protection to the metal on the contact surface, and other surface degrading conditions.